TINGKAT PERSEPSI REMAJA LAKI-LAKI DAN PEREMPUAN TENTANG PENCEGAHAN PANDEMI COVID DI DESA BARINGIN, LUBUK KILANGAN, PADANG - Deliani, Nurfarida; Rajab, Khairunnas; Kuriaya, Kunalan; Hanani, Silfia; Syawaluddin, Syawaluddin (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or better known as the Corona virus is a new type of Coronavirus that is transmitted to humans. This virus can attack anyone, from the elderly (old age groups), adults, children and babies, to pregnant women and breastfeeding mothers. The Covid-19 pandemic is felt by everyone, including teenagers. Advances in communication technology have made teenagers gain insight into Covid-19 from various sources, so that most teenagers ignore and a small proportion of teenagers care about the negative effects of Covid-19. The emergence of such behavior stems from different perceptions in understanding Covid-19. In this regard, the purpose of this study is to find out more about adolescents' perceptions of the Covid-19 pandemic based on gender. This research is a quantitative research with descriptive type. The samples of this research were 85 (eighty five) teenagers and their parents. The sampling technique was total sampling. The results of the study revealed that: it can be seen that all 32 male respondents (100%) had positive perceptions in preventing Covid-19 and a small proportion of female respondents had negative perceptions (3%) and 97% adolescents women have a positive perception in preventing Covid-19.